The Evaluation of Inquiry Learning Skills towards Math of Middle School Students in terms of Inquiring, Evaluating, Reasoning, and Reflective-Thinking Skills for Problem-Solving - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2020)
The purpose of the study was to develop a scale to determine inquiry learning skills perception towards math of middle school students, to test the developed scale, and to evaluate their inquiry learning skills towards math in terms of inquiring, evaluating, reasoning, and reflective thinking skills for problem-solving. For this purpose, the study was carried out within two stages. In the first stage, the availability of the scale was presented by analysing the reliability and validity of the scale. In the second stage, the relationships between inquiry learning skills towards math and inquiring, evaluating, reasoning, and reflective thinking skills for problem-solving were analysed by considering various variables. The second stage which was prepared according to relational scanning model was carried out with the participation of 217 middle school students. The following scales were used as data collection instruments; Inquiry Learning Skills Scale towards Math and A Reflective Thinking Skill Scale towards ProblemSolving. While middle school students had advance level of inquiry learning skills towards math, evaluating, reasoning, and reflecting thinking skills for problem-solving, and their inquiry skills were at intermediate level. There was a significant relationship between inquiry learning skills towards math and inquiring, evaluating, reasoning, and reflective thinking skills for problem-solving. Inquiry learning skills towards math differred significantly by students' gender, grade-levels, math achievement scores, and watching a science program for kids, but they did not differ by following a scientific magazine.
Keywords: Math; Inquiry learning; Problem-solving; Reliability; Validity; MATHEMATICS; EDUCATION; ACHIEVEMENT; TECHNOLOGY; MOTIVATION; ATTITUDES; GENDER; TOOLS; SCALE